The Influence of Job Embeddedness and Career Development on Employee Performance with Organizational Commitment as Variable Intervening: Study on Employees at Garment Factory in Semarang - Ariadi, Gede; Noegrahantie, Sofi Shellyana (Indonesian Journal Publisher, 2025)
This research examines the influence of job embeddedness and career development on employee performance with the mediating role of organizational commitment. This research uses a quantitative, explanatory approach with 100 respondents, employees of the Garment Factory in Semarang in the cutting department. The analysis in this research uses PLS-SEM (Partial Least Squares - Structural Equation Method). Based on the results of this research, it shows that: (i) job embeddedness influences employee performance; (ii) career development has no effect on employee performance; (iii) job embeddedness influences organizational commitment; (iv) career development influences organizational commitment; (v) organizational commitment influences employee performance; (vi) organizational commitment mediates the influence of job embeddedness on employee performance; Organizational commitment mediates the influence of career development on employee performance.